Determination of the melting layer from meteorological radar data in Malaysia - Khamis, N. H. H.; Sharif, O.A. R.; Hanzaz, Z.; Baharom, A. (2006)

(untitled)
A developed algorithm based on the vertical profile of radar reflectivity, has been applied to determine the boundaries of the melting layer and its thickness. The average values of the melting layer heights are compared with ITU-R recommendations and other obtained results in tropical regions at 500m resolution range. The results obtained showed lower values for heights of the melting layer.